(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze the role of Human Capital and Islamic Work Ethics in improving the performance of madrasah teachers in the context of community-based Islamic education. The research used a qualitative approach with an intrinsic case study design at MA Syahadat Nabatussalam Barurejo. Data were collected through participant observation, in-depth interviews with the madrasah principal and teachers, and institutional documentation. The results indicate that academic qualifications and ongoing training serve as professional standards that encourage teacher competency improvement. Furthermore, internalization of Islamic Work Ethics values, such as trustworthiness, responsibility, and work as worship, plays a role in fostering teacher discipline, loyalty, and moral commitment. The integration of professional competence and religious values ​​creates a pattern of teacher professionalism that is oriented not only toward academic achievement but also toward social and spiritual responsibility. The main finding of this study is the formation of the concept of Prophetic Professionalism, namely, teacher professionalism constructed by the structural demands of the institution and the social expectations of society, and legitimized by Islamic theological values. This research confirms that the integration of Human Capital and Islamic Work Ethics is a crucial strategy for sustainably improving madrasah teacher performance.